Cancer Australia consensus statement on COVID‐19 and cancer care: embedding high value changes in practice. Issue 10 (24th October 2021) - Milch, Vivienne; Wang, Rhona; Der Vartanian, Carolyn; Austen, Melissa; Hector, Debra; Anderiesz, Cleola; Keefe, Dorothy
Abstract: Introduction: Driven by the need to reduce risk of SARS‐CoV‐2 infection and optimise use of health system resources, while maximising patient outcomes, the COVID‐19 pandemic has prompted unprecedented changes in cancer care. Some new or modified health care practices adopted during the pandemic will be of long term value in improving the quality and resilience of cancer care in Australia and internationally. The Cancer Australia consensus statement is intended to guide and enhance the delivery of cancer care during the pandemic and in a post‐pandemic environment. This article summarises the full statement, which is available at https://www.canceraustralia.gov.au/covid‐19/covid‐19‐recovery‐implications‐cancer‐care . Main recommendations: The statement is informed by a desktop literature review and input from cancer experts and consumers at a virtual roundtable, held in July 2020, on key elements of cancer care that changed during the pandemic. It describes targeted strategies (at system, service, practitioner and patient levels) to retain, enhance and embed high value changes in practice. Principal strategies include: implementing innovative models of care that are digitally enabled and underpinned by clear governance, policies and procedures to guide best practice cancer care; enabling health professionals to deliver evidence‐based best practice and coordinated, person‐centred cancer care; and empowering patients to improve health literacy and enhancing their ability to engage in informed, shared decision making. Changes in management as a result of this statement: Widespread adoption of high value health care practices across all levels of the cancer control sector will be of considerable benefit to the delivery of optimal cancer care into the future.